Crystal structure of (Z)-3-(4-methoxybenzylidene)-2, 3-dihydrobenzo[b][1, 4]thiazepin-4(5H)-one. (January 2015) - Vinayagam, V.; Raj, J. Mohan; Murugavel, S.; Selvakumar, R.; Bakthadoss, M.
No abstract available